Peace through Order: Applying Augustine's Concepts of Society, Security and Conflict in a Disordered World - Gaumer, Matthew A. (Editorial Uniagustiniana, 2019)
The purpose of this chapter is to contextualize Augustine's world and show how that world shaped his understanding of the nature of war, peace and security, before identifying possible applications for today's geopolitical situations. The emphasis of this contribution is on connecting the reception of Augustine's thought with the current global environment, in order to assess how future challenges might be addressed, and to determine how stability, peace, and prosperity might be achieved for the maximum amount of people in the twenty-first century.